Mobility and transport for elderly and handicapped persons : proceedings of a conference held at Churchill College, Cambridge, England, 14-16 July 1981 under the auspices of Loughborough University of Technology, Florida State University, and the International exchange Center at the University of Florida /: proceedings of a conference held at Churchill College, Cambridge, England, 14-16 July 1981 under the auspices of Loughborough University of Technology, Florida State University, and the International exchange Center at the University of Florida. (2021) - Unknown
No abstract available